1986
DOI: 10.2307/3576742
|View full text |Cite
|
Sign up to set email alerts
|

Selective Gene Amplification in Mammalian Cells after Exposure to 60 Co g Rays, 241 Am a Particles, or uv Light

Abstract: Simian Virus 40 wild type (SV40)-transformed Chinese hamster embryo cells (Co631) contain about five viral copies integrated per cell genome. These SV40 sequences were used as endogenous indicator genes to study the response of mammalian cells to radiation at the gene level. An increase in copy number was detected by dispersed cell blotting and Southern analysis in combination with specific DNA hybridization. All types of radiation tested induce a 15- to 25-fold amplification of SV40 sequences without producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

1987
1987
1993
1993

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Exposure of simian virus 40 (SV40)-transformed CHO cells to UV radiation resulted in amplification of integrated SV40 sequences (Lavi and Etkin, 1981). Lucke-Huhle et al (1986) showed that UV-irradiation of SV-40-transformed CHO cells resulted in a 15-to 25-fold amplification of SV40 sequences without producing intact virus. This amplification was selective in that other genes, such as DHFR, K-ras, Ha-ras and aactin, were not expressed in abnormally high copy numbers.…”
Section: Cooperation Between Oncogenesmentioning
confidence: 99%
“…Exposure of simian virus 40 (SV40)-transformed CHO cells to UV radiation resulted in amplification of integrated SV40 sequences (Lavi and Etkin, 1981). Lucke-Huhle et al (1986) showed that UV-irradiation of SV-40-transformed CHO cells resulted in a 15-to 25-fold amplification of SV40 sequences without producing intact virus. This amplification was selective in that other genes, such as DHFR, K-ras, Ha-ras and aactin, were not expressed in abnormally high copy numbers.…”
Section: Cooperation Between Oncogenesmentioning
confidence: 99%
“…Nonpermissive rodent cells (e.g., the SV40-transformed Chinese hamster embryo cell line Co631) can be induced to asynchronous SV40 replication by treatment with any one of a number of DNA-damaging agents (12,21,23,25,26,35). The induced replication resembles that in permissive cells: T antigen is required, and initiation occurs at the SV40 origin.…”
mentioning
confidence: 99%
“…Because of limited information on the human replicon and how origins of replication are controlled in cis, viral systems have proven to be most useful to the study of mechanisms of replication and gene amplification (5,15,17,23,24,27,29,33,38,39,44,53,54,60). Papovaviruses and parvoviruses can be induced to replicate in various cell lines (permissive or nonpermissive) when the cells are treated with a variety of DNA-damaging agents (38,53,60).…”
mentioning
confidence: 99%